The relationship between place and hallmark event in a socio-cultural context / Musaddiq Mohamad - Mohamad, Musaddiq (2015)
The tourism industry has been one of the key to economic growth globally, and as the second after manufacturing industry, particularly here in Malaysia (Thomas, 2012). With the scale of attracting bigger attention of audiences towards a cultural event, Hallmark event has always been the best solution. However, most empirical studies are focusing on the categorization of places rather than the socio-cultural impacts of a chosen place, town, city, or region which hallmark event takes part. Hallmark event has always played a huge sentimental role in promoting event and places in Malaysia. This study attempts to enrich the previous semantic-tangle on the definitions of place and how they relate with hallmark event socio-cultural impact. This study examines four main factors in studying the relationship between place and hallmark event in a context of socio-culture, which are loci/space, people/social, event/experience, and cultural impacts. The chosen Hallmark event was Malacca Art and Performance (MAP) festival, which is one of the well-known events happening in Malaysia each year attracting strong art enthusiast and lovers all around the globe towards one UNESCO rated destination. Systematic observation and surveys have been distributed towards 100 convenience sampling audience of MAP festival 2013, coming from background such as local visitors, tourist, host community and organizers. The proposed framework and hypothesis given to support finding that they are strong valid correlation between loci/space, people/social, event/experience, and cultural impacts with hallmark event impact. It has been found that, this positive relationship of wellplanned and managed event would result into spectacular impact of audience not only lifting the event higher but also the socio-cultural acceptance and awareness towards the importance of hallmark event and tourism industry. It is recommended that place (loci, people, and event) should be considered by authorities before conducting Hallmark Event.